2017
DOI: 10.1002/wrna.1448
|View full text |Cite
|
Sign up to set email alerts
|

A jack of all trades: the RNA‐binding protein vigilin

Abstract: The vigilin family of proteins is evolutionarily conserved from yeast to humans and characterized by the proteins' 14 or 15 hnRNP K homology (KH) domains, typically associated with RNA-binding. Vigilin is the largest RNA-binding protein (RBP) in the KH domain-containing family and one of the largest RBP known to date. Since its identification 30 years ago, vigilin has been shown to bind over 700 mRNAs and has been associated with cancer progression and cardiovascular disease. We provide a brief historic overvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 84 publications
(397 reference statements)
4
33
0
Order By: Relevance
“…Our results combined with the known role of RRBP1 and vigilin in translation of cellular mRNAs 32,33 suggests that the RBPs stimulate viral RNA replication, at least partially, by promoting translation of the viral polyprotein. Aside from translation, both vigilin and RRBP1 can also act on the stability of their target mRNAs 34,35 .…”
Section: Cellular Rbps Contribute To Denv Genomic Rna Stabilitysupporting
confidence: 55%
“…Our results combined with the known role of RRBP1 and vigilin in translation of cellular mRNAs 32,33 suggests that the RBPs stimulate viral RNA replication, at least partially, by promoting translation of the viral polyprotein. Aside from translation, both vigilin and RRBP1 can also act on the stability of their target mRNAs 34,35 .…”
Section: Cellular Rbps Contribute To Denv Genomic Rna Stabilitysupporting
confidence: 55%
“…For some, such as the KSR protein, all four of its KH domains contribute to RNA binding (Hollingworth et al, 2012). For many others, such as the vigilin and ZBP1 proteins, RNA binding is conferred by a specific subset of KH domains (Nicastro et al, 2017;Nicastro et al, 2015;Cheng and Jansen, 2017). Our results provide evidence that the Bicc1 N-terminal region functions similarly to the latter category of multi KH-containing RNA-binding domains.…”
Section: Discussionmentioning
confidence: 66%
“…We first confirmed that translational repression of target mRNAs by vigilin ( Figure 1 ). It is known that vigilin binds a large number of mRNAs (estimated 700 mRNAs; [12] ). We demonstrate that vigilin directly interacts with the pyrimidine-rich element in the CSF-1R mRNA 3′UTR, and requires the full-length 69 nt for stable binding ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data on its role in cancer and the underlying mechanism is still limited. Further, it is recognized that while many of vigilin's known actions occur in the cytoplasm, vigilin's nuclear functions are less well understood [12] .…”
Section: Introductionmentioning
confidence: 99%